2002
DOI: 10.1177/088307380201700811
|View full text |Cite
|
Sign up to set email alerts
|

Review Article : Cognitive Deficits in Neurofibromatosis 1

Abstract: Cognitive deficits and academic learning difficulties are the most common neurologic "complication" of neurofibromatosis 1 in childhood and can be responsible for significant lifetime morbidity. There is a slight increase in the frequency of mental retardation (Wechsler Full-Scale IQ < 70) in children with neurofibromatosis 1, but the mean Full-Scale IQ for the patient group is within 1 SD of the population mean. Academic difficulties are common, as are specific deficits in visuospatial ability, executive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 42 publications
2
87
0
7
Order By: Relevance
“…Beyond intellect, studies have found specific deficits in visual perception, most consistently on the Benton Judgment of Line Orientation (JLO) task (Rowbotham et al 2009;Hyman et al 2005;Schrimsher et al 2003;Benton et al 1983), along with more generalized difficulties in the areas of language development (Hyman et al 2005), executive functioning (Templer et al 2012;Roy et al 2010;North et al 2002), and attention (Templer et al 2012;North et al 2002). Understanding of these deficits has helped to guide intervention trials and clinical practice with the NF1 population, shaping assessment and intervention practices.…”
mentioning
confidence: 99%
“…Beyond intellect, studies have found specific deficits in visual perception, most consistently on the Benton Judgment of Line Orientation (JLO) task (Rowbotham et al 2009;Hyman et al 2005;Schrimsher et al 2003;Benton et al 1983), along with more generalized difficulties in the areas of language development (Hyman et al 2005), executive functioning (Templer et al 2012;Roy et al 2010;North et al 2002), and attention (Templer et al 2012;North et al 2002). Understanding of these deficits has helped to guide intervention trials and clinical practice with the NF1 population, shaping assessment and intervention practices.…”
mentioning
confidence: 99%
“…Medical records of 75 patients (34 males and 41 females) diagnosed with NF1 based on standard clinical criteria 8) and who underwent brain MRI and PET between Jan 2005 and Dec 2011 were evaluated retrospectively. Patients who had intracranial tumors or who under went cranial surgery were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Pathologically, UBOs may represent increased fluid within myelin associated with hyperplastic or dysplastic glial proliferation. 5) Although there have been several reports showing an association between UBOs and various clinical manifestations of NF1, including Lisch nodules, subcutaneous neurofibromas, optic glioma, other central nervous system neoplasms, cognitive deficits, and learning disabilities, [6][7][8] the …”
Section: Introductionmentioning
confidence: 99%
“…Neurocognitive sequelae in neurofibromatosis type 1 (NF1) have been well-documented and result in significant morbidity and dysfunction in children, adolescents, and adults with the disease. [1][2][3][4][5][6][7] Research has documented phenotypic patterns of cognitive dysfunction in NF1, as well as the functional impact these deficits have on individuals in naturalistic settings such as school and work. [8][9][10][11] Despite the high prevalence and significant morbidity of cognitive impairments, few intervention trials have targeted cognitive dysfunction as a primary endpoint.…”
Section: Introductionmentioning
confidence: 99%